2023
DOI: 10.3390/jof9030286
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli, but Not Staphylococcus aureus, Functions as a Chelating Agent That Exhibits Antifungal Activity against the Pathogenic Yeast Candida albicans

Abstract: Humans are colonized by diverse populations of microbes. Infections by Candida albicans, an opportunistic fungal pathogen, are a result of imbalances in the gut microbial ecosystem and are due to the suppressed immunity of the host. Here, we explored the potential effects of the polymicrobial interactions of C. albicans with Staphylococcus aureus, a Gram-positive bacterium, and Escherichia coli, a Gram-negative bacterium, in dual and triple in vitro culture systems on their respective growth, morphology, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The biofilm assay was carried out as described previously [ 29 ]. Briefly, the overnight-grown fungal cultures were diluted up to an OD600 of 0.5 in YPD nutrient media.…”
Section: Methodsmentioning
confidence: 99%
“…The biofilm assay was carried out as described previously [ 29 ]. Briefly, the overnight-grown fungal cultures were diluted up to an OD600 of 0.5 in YPD nutrient media.…”
Section: Methodsmentioning
confidence: 99%
“…The fungal inoculum for various fungal infections was conducted by using standard protocol (Bose et al, 2023 ; Kumari et al, 2023 ; Patel et al, 2023 ; Peroumal et al, 2019 ). The live and heat-killed (HK) CNA25 inoculums were prepared from the same pre-culture.…”
Section: Methodsmentioning
confidence: 99%
“…To starve pathogens of essential metals, the host organism employs nutritional immunity strategies to reduce the availability of metals, thereby the virulence and disease progression of a pathogen is suppressed drastically 1719 . Our recent report found that a soluble factor released from E. coli during co-culturing inhibited the growth, biofilm formation, and morphological transition from yeast to hyphae of C. albicans 20 . In an animal model, the culture supernatant of E. coli attenuated the virulence of C. albicans significantly.…”
Section: Introductionmentioning
confidence: 92%
“…In an animal model, the culture supernatant of E. coli attenuated the virulence of C. albicans significantly. Chemical complementation analyses revealed that the exogenous addition of divalent metals rescued the growth of C. albicans that was inhibited by E. coli 20 . Based on the concept of nutritional immunity and these reports, we argued that the metal chelators like EDTA, DTPA, etc.…”
Section: Introductionmentioning
confidence: 99%